1988
DOI: 10.1111/j.1464-410x.1988.tb13971.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Combination Therapy with Flutamide in Patients Relapsing after Castration

Abstract: Two hundred and nine patients with biopsy-proven stage D2 prostatic carcinoma showing disease progression after orchiectomy or treatment with DES (stilboestrol) or an LHRH agonist alone received combination therapy with the pure antiandrogen flutamide. In patients treated with DES, the oestrogen was replaced by the LHRH agonist [D-Trp6]LHRH ethylamide. The objective response to therapy was assessed according to the criteria of the US NPCP. Thirteen patients had a complete response to treatment, while partial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…The results obtained will suggest the most suitable hormonal therapy for hormone-refractory metastatic PCa in which specific agonists or antagonists will be recommended or advised against on a patientby-patient basis. For instance, it is known that androgen ablation causes more than a 90% reduction in plasma testosterone level, but only a slight decrease in plasma adrenal androgen levels (46) and the results obtained with mutants AR T877A and AR C685Y show that they were both responsive to androstenedione, an adrenal androgen with which wild-type AR binds with low affinity. Thus blocking the activity of the remaining androstenedione or, even more, reducing its plasma level with glucocorticoids may be worth considering as a more appropriate treatment of PCas that express such mutant ARs.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained will suggest the most suitable hormonal therapy for hormone-refractory metastatic PCa in which specific agonists or antagonists will be recommended or advised against on a patientby-patient basis. For instance, it is known that androgen ablation causes more than a 90% reduction in plasma testosterone level, but only a slight decrease in plasma adrenal androgen levels (46) and the results obtained with mutants AR T877A and AR C685Y show that they were both responsive to androstenedione, an adrenal androgen with which wild-type AR binds with low affinity. Thus blocking the activity of the remaining androstenedione or, even more, reducing its plasma level with glucocorticoids may be worth considering as a more appropriate treatment of PCas that express such mutant ARs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have shown that intratumoral concentrations of T and 5α-dihydrotestosterone (DHT) sufficient to activate AR-dependent transcription are maintained in CRPC despite suppression of serum T (3)(4)(5)(6). The requirement for the intratumoral generation of androgen ligand is exemplified by frequent and often sustained responses to AR antagonists (7,8), as well as an unprecedented prolongation of survival in chemotherapy-refractory metastatic CRPC conferred by abiraterone acetate, a potent inhibitor of CYP17A1, which is required for the synthesis of adrenal 19-carbon steroid precursors of T and DHT (9).…”
mentioning
confidence: 99%
“…Among androgens it is unique in that both HF and casodex failed to block significantly Adiol-induced AR transactivation in prostate cancer cells. Because castration with or without combination therapy with antiandrogen decreases the serum concentration of Adiol by only 40-50% (20,21), our previous findings suggested that current combined androgen blockade treatment might be insufficient to block Adiol's action in AR-positive prostate cancer. Therefore, we determined whether ADEK inhibited Adiol-induced AR transcription by measuring MMTV-Luc activity.…”
Section: Anti-dht Effect Of Adek On Psa Expression and Cell Proliferamentioning
confidence: 92%